UV radiation recruits CD4+GATA3+ and CD8+GATA3+ T cells while altering the lipid microenvironment following inflammatory resolution in human skin in vivo. Issue 4 (2nd April 2020) - Hawkshaw, Nathan J; Pilkington, Suzanne M; Murphy, Sharon A; Al‐Gazaq, Norah; Farrar, Mark D; Watson, Rachel EB; Nicolaou, Anna; Rhodes, Lesley E
Abstract: Objectives: Solar ultraviolet radiation (UVR) has major adverse effects on human health. While the mechanisms responsible for induction of UVR‐induced inflammation are well‐documented, the mediation of its resolution and longer‐term adaptive homeostasis is unknown. Therefore, we examined the skin immune and lipid profile over time following UVR inflammation. Methods: To investigate the self‐resolving events of UVR inflammation in vivo, human skin was exposed to a single pro‐inflammatory dose of UVR. Skin biopsies and suction blister fluid were taken at intervals up to 2 weeks post‐UVR. The immune infiltrate was quantified by immunohistochemistry, and lipid mediators were profiled by liquid chromatography/mass spectrometry. Results: We identified that cellular resolution events including switching of macrophage phenotype apply to human sunburn. However, UVR‐induced inflammation in humans involves a post‐resolution phase that differs from other experimental models. We demonstrate that 2 weeks after the initiating UVR stimulus, there is considerable immune activity with CD8 + GATA3 + T cells maintained in human skin. Our results challenge the dogma of CD4 + FOXP3 + T cells being the main effector CD4 + T‐cell population following UVR, with CD4 + GATA3 + T cells the dominant phenotype. Furthermore, lipid mediators are elevated 14 days post‐UVR, demonstrating the skin lipid microenvironment does not revert to the tissue setting occurring prior to UVR exposure. Conclusion: We have identified for the first time that CD4 + GATA3 + and CD8 + GATA3 + T‐cell subpopulations are recruited to UVR‐inflamed human skin, demonstrating discrepancies between the adaptive UVR response in mice and humans. Future strategies to abrogate UVR effects may target these T‐cell subpopulations and also the persistent alteration of the lipid microenvironment post‐UVR. Abstract : Hawkshaw et al. demonstrate that, in the post‐resolution phase following acute UVR inflammation in human skin, CD8 + GATA3 + cells are recruited and associated with an altered bioactive lipid profile. In contrast to murine models, CD4 + GATA3 + T cells and not CD4 + FOXP3 + cells predominate.